URBAN PLANNING, DEMOLITION OF PROPERTY AND CITIZENS’ DEPRIVATION IN AFRICAN CITIES: A POLYCENTRIC PLANNING PERSEPCTIVE - Samson AKINOLA (Journal of Construction Project Management and Innovation)
This paper used the Institutional Analysis and Development (IAD) framework to analyse the missing links between urban managers and urban residents in Angola, Ghana and Kenya. The paper found that urban governance structures in the three countries are centralised and deviate from planning norms and people-centred governance, hence urban managers and citizens are not operating in synergy. The rapidly growing urban population makes infrastructure to be deteriorating; thus, creating slums and squatter settlements that warrant eviction and demolition by governments. Eviction and demolition generate adverse consequences on socio-economic wellbeing of citizens – property destroyed, while children education was affected. This paper provides case studies to demonstrate principles and practices needed to make polycentric planning and community initiatives resolve conflicts of interests on urban space. The paper argues that, for urban governance to benefit urban residents, it has to proceed from the people and be guided by them in decisions on all urban matters, including planning and modification of plans on competing urban landuses. Using Polycentric Planning and Poverty Reduction Strategy (PPPRS), this paper designs an African Polycentric Urban Environmental Governance Model (APUEGM) capable of mainstreaming citizens-centred institutions in urban areas into socio-economic and political decision making so that citizens (including the urban poor) can participate effectively in decisions on redevelopment, thus entrenching good urban governance, citizens-centred environmental planning and development in Africa.